Temporal Distribution of Arsenic and Metals in Soil From King George Island, Antarctica - Trevizani, Tailisi H.; Montone, Rosalinda C.; Figueira, Rubens C. L. (Frontiers in Marine Science, 2022)
The polar regions are vulnerable to impacts caused by local and global pollution. The Antarctic continent has been considered an environment that has remained little affected by human activities. Direct exposure to contaminants may occur in areas continuously occupied by research stations for several decades. Admiralty Bay on the southeast coast of King George Island, has potential for being affected by human activities due research stations operating in the area, including the Brazilian Commandant Ferraz Antarctic Station (CFAS). The levels of metals and arsenic were determined in soils collected near CFAS (points 5, 6, 7, and 9), Base G and at two points distant from the CFAS: Refuge II and Hennequin. Samples were collected after the fire in CFAS occurred in February 2012, up to December 2018 to assess the environmental impacts in the area. Al and As were related with Base G. Refuge II and Hennequin can be considered as control points for this region. As a consequence of the accident, the increased levels for Cd, Cu, Pb, and Zn, especially at point 9 (inside the CFAS) and in the soil surrounding the CFAS in 2013. The results from 2016 to 2018 demonstrated a reduction in levels of all studied metals near CFAS, which may be related to the leaching of metals into Admiralty Bay; it is thus, being important the continue monitoring soil, sediments, and Antarctic biota.